Management of lymphadenitis due to non-tuberculous mycobacterial infection in children. - Scott, C; Atkinson, S; Sodha, A; Tate, C; Sadiq, J; Lakhoo, K; Pollard, A (2012)
PURPOSE: Non-tuberculous mycobacterial (NTM) infection is an important cause of cervico-facial lymph node enlargement in young children. The optimal treatment is thought to be early complete excision without chemotherapy. We compared management of patients referred to our centre to this "gold standard" and determined clinical outcomes by type of primary surgical intervention (complete excision vs. incomplete excision). METHODS: Retrospective study of management and clinical outcomes of all children (<12 years) with NTM lymphadenitis referred to a single UK centre between May 1998 and May 2008. RESULTS: We identified 43 children. Median time from onset of swelling to operation was 6 weeks. Management was: no operation (n = 1, 2 %), complete excision (n = 20, 47 %), incision and drainage (n = 17, 40 %) and fine needle aspirate (n = 5, 12 %). Children not treated by primary complete excision were more likely to have: re-operation (91 vs. 30 %; χ(2) = 16.48; p < 0.0001); persistent lymphadenitis (77 vs. 30 %; χ(2) = 9.45; p = 0.002); sinus formation (26 vs. 5 %; χ2 = 3.74; p = 0.05). CONCLUSION: Failure to undertake primary complete excision leads to further morbidity. A high index of suspicion is required for timely appropriate management to avoid unnecessary morbidity and further intervention.